(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Artificial insemination (AI) is one of the most important tools for upgrading the cattle breed in our country. The present study was conducted to determine the conception rate of Local and Crossbred cattle of Bangladesh using field data. In this study, 78 AI service providers named as Livestock Assistants (LAs) having at least two years of work experience with ACI Animal Genetics were randomly chosen from 28 districts of the 8 divisions. Information was collected randomly from 417 selected farmers whose 417 cattle were inseminated in March 2022. The majority of the cattle raised by the farmers were crossbred (79% of the total cattle). These 417 cattle were inseminated using five different genotypes of sire’s semen (Holstein Friesian 100%, Holstein Friesian cross, Sahiwal 100%, Sahiwal cross, and RCC). The study revealed that the overall conception rate of cattle was 70%. However, the rates of conception vary among the different genetic groups of cattle. Among the different groups, the RCC had the highest conception rate (100%) followed by the indigenous (74%), Sahiwal cross (72%), and Holstein Friesian cross (62%). Our study also revealed that, of the 30% of repeat cases, 17% required a second insemination, 7% a third or more insemination for getting pregnant and 6% of the cows failed to become pregnant. About 96% farmers received AI cards, but only 67% of them mentioned that they preserved those AI cards for future uses. In a nutshell, this study disclosed the genotype wise first service conception rate in Local and Crossbred cattle at the field level of Bangladesh. J Bangladesh Agril Univ 22(2):202-209, 2024